GREEN EXERCISE AND CARDIOVASCULAR HEALTH: QUANTITATIVE EVIDENCE FROM A COMMUNITY CONSERVATION INTERVENTION IN THE UK - Christie, Mark; Miller, Paul K.; Dewhurst, Susan (European Scientific Journal, ESJ, 2015)
This paper aims to add to the fledgling body of work pertaining to the cardio-vascular benefits of self-motivated activity in naturalistic settings. Collecting results from a longitudinal study of a regional community conservation intervention in the UK, it is found that - across a wide range of age groups – simple engagement with a set of everyday horticultural tasks induces the exact levels of exercise that the medical and sport sciences define as optimal for the maintenance of everyday baseline fitness. It is further contended, in line with prior literature, that such capital-free initiatives, designed to improve a local social environment can, thereby, improve the core heath of individuals who may be averse to more conventional gym-type environments.